Study of Rutile TiO2 band structures and optical properties using Density functional theory (DFT) - Rafea A. Munef; Abdulhadi M. Ghaleb; Ahmed Th. Shihatha (Tikrit Journal of Pure Science, 2021)
In this article, a theoretical analysis to measure the band composition, optical properties and density of states (DOS) of rutile titanium dioxide was conducted via the castep simulation program. Calculations of the first principles were carried out using the super cell (1x1x1) process. The first computation of  concepts was studied by density functional theory (DFT) with a generalized gradient approximation from Perdew-Wang's 1991 (GGA-PW91), local density approximation (LDA) for exchange-correlation energy functional, and (LDA)+U method, implementation of coulomb interactions btween   of ( ) atom  and  of (  ) atom.All experimental values are agreed with our results. The results for LDA and GGA-Pw91 indicated weaknesses in the estimation and far from the experimental results for the properties of the  rutile under analysis, except for the energy band difference, although the estimation data (LDA) + U was in accordance with the experimental values. The optical properties of rutile  was obtained using several methods of exchange correlations, well in accordance with experimental findings and other theoretical evidence.